Efficient inter mode selection algorithm for H.264 - LU Lu; ZHOU Wei (Tongxin xuebao, 2006)
Motion estimation was introduced by H. 264 video coding standard with multiple block sizes to achieve a con- siderably higher coding efficiency than other video coding algorithms. However, this comes at the greatly increased computing complexity at the encoder. A method was proposed to eliminate some redundant coding modes that contribute very little coding gain based on analysis of macroblock detail-level and texture directions. The simulation results show that the algorithm can remarkably decrease the complexity at the encoder while keeping satisfying coding efficiency.